Lifestyle Medicine Inpatient Consultation Services at Loma Linda University Health: A Novel Approach in a Tertiary Care Center. Issue 3 (May 2018) - Cramer, Tonya; Wilson, April; Rea, Brenda
As a nation facing primary care provider shortages, an expanding chronic disease burden, and rising health care costs, lifestyle medicine interventions have become critical for patient care and management. The current fee-for-service health care system in the United States is designed for delivering acute care but has made it challenging to deliver and be reimbursed sufficiently for lifestyle interventions that can help prevent and treat chronic disease. Loma Linda University Health began to address these concerns through the creation of an inpatient consultation service for the neurology rehabilitation stroke team. Initiation of the consultation service took 2 years of planning, testing, and resource development. Currently, the consultation service operates one half-day per week in the rehabilitation hospital utilizing 1 attending physician and 2 residents. Visiting residents and medical students are also permitted to rotate with the new service. In coordination with billing experts, a standard number of 21.2 to 25.4 RVUs (relative value units) has been established for the half-day service. As the service continues to expand, future considerations include adding consultation availability to other departments and increasing the consultation workforce.